Analisis Tingkat Resapan Air Menggunakan Sistem Informasi Geografis di Das Tabunio - Ahmad Eko Saputra; Ichsan Ridwan; Nurlina Nurlina (Jurnal Fisika FLUX, 2019)
The development of development that is so rapid causes more and more land to change into new buildings and settlements that have an impact on the reduction in the area of water catchment areas. Reduced water catchment areas will result in reduced groundwater reserves and will cause natural disasters such as floods. Based on this, efforts need to be made to determine the condition and distribution of water absorption in the Tabunio watershed area. In determining water absorption conditions there are four parameters, namely soil type, rainfall, land cover and slope. The data analysis method used is the overlay method with Geographic Information System (GIS) software. The results of data analysis showed that the study area with an area of 62,558.56 ha was divided into five conditions for water catchment areas. The water recharge conditions were very critical with an area of 32.38 ha, critical conditions covering 13,391.14, rather critical conditions covering an area of 35,769.47 ha, critical conditions ranging from 13,359.27 ha and natural normal conditions covering an area of 6.10 ha.